Cache prefetching strategy based on selective Markov model - CAI Wei-hong1; XIAO Shui2; WEI Gang1; XIONG Zhi2; HUANG Min-hua2 (Tongxin xuebao)
Through analyzing the existing streaming media cache management algorithm and user’s watching behavior characteristics,a new cache prefetching strategy based on selective Markov model was presented.The strategy,by mod-eling the user’s VCR action of choosing the merging sequence method,applied the FPVlike method to get the selective Markov model FPMMVlike and built a streaming media proxy cache prefetching mechanism FPVlike-LRU-2 by com-bining the replacement algorithm LRU-2.The experimental results show that,FPVlike-LRU-2 is 10%、12%、17% higher than FPLRU-2,SPLRU-2 and LRU-2 respectively in reducing latency experienced by users,and this value is able to reach over 60% in the ideal situation.